2017
DOI: 10.3390/pathogens6040062
|View full text |Cite
|
Sign up to set email alerts
|

Liposomal and Deoxycholate Amphotericin B Formulations: Effectiveness against Biofilm Infections of Candida spp.

Abstract: Background: candidiasis is the primary fungal infection encountered in patients undergoing prolonged hospitalization, and the fourth leading cause of nosocomial bloodstream infections. One of the most important Candida spp. virulence factors is the ability to form biofilms, which are extremely refractory to antimicrobial therapy and very difficult to treat with the traditional antifungal therapies. It is known that the prophylaxis or treatment of a systemic candidiasis are recurrently taken without considering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 101 publications
1
16
1
Order By: Relevance
“…An earlier study showed that C. parapsilosis biofilms were resistant to d-AMB and susceptible to lipid formulations of AMB (both lipid complex and liposomal) [28]. Conversely, our results are in agreement with recently published data demonstrating good activity of d-AMB on the biomass reduction of C. parapsilosis biofilms [38,39]. Moreover, a previous study showed higher activity of d-AMB than ANF against C. parapsilosis biofilms [39], in agreement with our results, which extend this observation to CAF and MIF.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…An earlier study showed that C. parapsilosis biofilms were resistant to d-AMB and susceptible to lipid formulations of AMB (both lipid complex and liposomal) [28]. Conversely, our results are in agreement with recently published data demonstrating good activity of d-AMB on the biomass reduction of C. parapsilosis biofilms [38,39]. Moreover, a previous study showed higher activity of d-AMB than ANF against C. parapsilosis biofilms [39], in agreement with our results, which extend this observation to CAF and MIF.…”
Section: Resultssupporting
confidence: 93%
“…Biofilm formation by C. parapsilosis has shown a high degree of variability among isolates [5,36] and the antibiofilm activity of d-AMB has been reported to be species and strain dependent [37,38]. An earlier study showed that C. parapsilosis biofilms were resistant to d-AMB and susceptible to lipid formulations of AMB (both lipid complex and liposomal) [28].…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the liposomal formulation of amphotericin B is found to be more effective in the eradication of the biofilm cells for all the Candida spp. than deoxycholate formulation. Echinocandin tolerance was not detected in the present study.…”
Section: Discussioncontrasting
confidence: 76%
“…The formation of Candida species biofilms raises significant clinical issues because of an additional increase in antifungal drug resistance, as well as increased evasion of host immune defenses. Furthermore, biofilm development on medical devices can cause the failure of the device and may turn into a source of future infection [9].…”
Section: Introductionmentioning
confidence: 99%